Experimental and analytical analysis for bending load capacity of old timber beams with defects when reinforced with carbon fiber strips. (15th February 2018) - Rescalvo, Francisco J.; Valverde-Palacios, Ignacio; Suarez, Elisabet; Gallego, Antolino
Abstract: This paper describes a comparative experimental and analytical study of the maximum bending load in timber beams of Pinus sylvestris L . having natural defects (knots, grain deviations, fissures and wanes) that are reinforced with carbon fiber composite (CFRP). Beams extracted during rehabilitation of the roof frame of the School of Law, University of Granada, had been in service for over two hundred years. Two commercial CFRP pultruded laminates were applied as reinforcement, for comparison. Both were properly glued with epoxy resin on the tension side of the beams, partially covering the area on this side. It is clearly shown that, due to the abundance of defects, using the elastoplastic constitutive law of timber and assuming the same tension and compression elastic moduli in the cross-section equilibrium method, the analytical values for the bending load capacity will not match the experimental ones. However, this assumption has been traditionally used in most previous research on timber beams reinforced with composite materials. As an alternative, a more general model for the timber may be used, in which the two moduli are considered to be different in compression and tension stresses. Results demonstrate how this modification provides a much better match between analytical and experimental values of the bending load capacity. The improvement is especially evident for beams with natural defects and many years in service, reinforced with CFRP for rehabilitation purposes. Moreover, a better mechanical behavior of the reinforced specimens is obtained, when compared with the control ones (without reinforcement): reinforcement induced an improvement of up to 88% in bending load capacity.